Superconducting quark matter in the Chromodielectric Model - Linares, L.; Malheiro, M.; Fiolhais, M.; Taurines, A. R. [UNESP] (AIP Publishing, 2004)
In this work we study the strange quark matter in an extented version of the Chromodielectric Model (CDM) with a BCS quark pairing implemented, and analyze the superconducting color flavor locked (CFL) phase. We compare the equation of state and the stability of the strange quark matter from QCD in the CFL phase with the superconducting version of the CDM. In the CDM there is a confining potential which originates a dynamical bag constant in the sense that its value depends on the density. Our results indicate that the inclusion in the energy density of the pairing quark interaction allows for an absolutely stable quark matter state even for large potential energies, preventing the metastability of quark matter found in the CDM at high densities.